A checklist of peritrich ciliate epibionts (Ciliophora, Peritrichea) on aquatic oligochaetes (Annelida, Oligochaeta) - Chatterjee, Tapas (Zootaxa, 2025)
A review of the peritrich ciliate epibionts (Ciliophora, Peritrichea) associated with aquatic Oligochaeta (Annelida) is presented, based on published records. Twenty-two peritrich species, along with four organisms classified to the genus level and two unidentified peritrichs, have been documented as epibionts on oligochaetes. Oligochaetes in the family Naidae presented the highest occurrence and diversity of associated ciliates. Most cases ciliates were predominantly attached on the posterior end of oligochaetes. Ciliate hyperepibiosis on oligochaetes was also observed.